THE EFFECT OF USING MATHEMATICAL SOFTWARE IN UNDERSTANDING MATERIAL IN STATISTICS COURSES - Akbar Nasrum; Supratman Supratman (JME (Journal of Mathematics Education), 2019)
This research was conducted at the Sembilanbelas November Kolaka University. This study aims to show the effect of the use of software in learning on the understanding ofstatistical material. The material discussed is the data normality test. To achieve that goal the researcher measures the understanding of student material before and after use of the software. Next, data analysis is done by comparing the results of the pre-testand post-test that have been obtained. The final result of the study shows that use mathematical software has a very significant effect of statistical material understanding, especially in data normality testing.